Epidemiology of duck as reservoir of Avian Influenza Virus in Bangladesh - Hassan, Md Zakir; Rahman, Md Mamunur; Das, Bidhan Chandra; Amin, Md Al; Sultana, Salma; Ferdouse, Humaira; Jaber, Md; Rahman, Md Shajedur; Hoque, Md Fazlul (Asian Journal of Medical and Biological Research, 2018)
This research work was conducted to detect the prevalence and incidence of Avian Influenza Virus (AIV) in Duck at hoar area of Kishorganj district in Bangladesh. The study period was July 2013 to December 2013 and the molecular work was done in Central Disease Investigation Laboratory (CDIL), Dhaka. A total number of 736 blood serum sample and 150 cloacal swab sample were collected from asymptomatic semi scavenging duck above 4 month of age. Blood serum sample was tested to detect the prevalence of Avian Influenza Virus A (AIV) specific antibody through indirect Enzyme Linked Immunosorbent Essay (ELISA) and cloacal sample was tested to detect the incidence of AIV through real time Polymerase Chain reaction (PCR). A total number of 736 blood serum sample were tested in which 684 is positive (+ve) of Avian Influenza type A antibody and 52 are negative (-ve) of Avian Influenza type A. The prevalence rate was 92.93%. The tested result shown that prevalence rate was in 4-6 month of age as 93.96%, as 7-9 month of age as 92.92 % and in 10-12 month of age as 91.91%. A total number of 15 pooling sample from 75 cloacal samples was conducted for detection of AIV that shed in environment. After calculating the result through real time Reverse Transcription (RT) - PCR, it was shown that 2 pooling sample was positive (13.33%) for AIV and 13 pooling sample was negative (86.87%) for AIV. So incidence rate was 13.33% for AIV. This duck can transmit the AIV in the surrounding poultry population and clinical outbreaks may occur. After analysis of ELISA & PCR result it was shown that duck act as a natural reservoir of AIV in Bangladesh. Asian J. Med. Biol. Res. March 2018, 4(1): 14-20